Sustainable Reporting Strategies: An Analytical Review of the Integration of ESG (Environmental, Social, and Governance) Factors in Financial Statements - Alfiana; Ari Purwanti; Humaidah Muafiqie (Universitas Tidar, 2023)
This comprehensive research delves into the seamless integration of Environmental, Social, and Governance (ESG) factors within the financial disclosures of 120 manufacturing enterprises situated in West Java. Employing a multifaceted approach encompassing content analysis, in-depth interviews, and comprehensive stakeholder surveys, this study uncovers sustainable reporting strategies and conducts an in-depth assessment of ESG integration. Furthermore, it diligently explores stakeholder perceptions surrounding these integrations. The results obtained from this extensive investigation portray a landscape marked by substantial ESG disclosures within the financial reports, with a particular emphasis on environmental aspects. Interviews conducted as part of the study brought to light a myriad of motivations, challenges, and innovative strategies employed by these manufacturing companies. Meanwhile, the stakeholder surveys were a testament to the growing reliance on ESG information as a critical decision-making resource. The study's findings offer guidance for manufacturing businesses seeking to achieve a harmonious integration of economic growth, social responsibility, and environmental stewardship. By enhancing transparency, accountability, and responsible practices, these companies may foster sustainable development not just in West Java but also in other regions.